2007
DOI: 10.1097/jom.0b013e31802df12c
|View full text |Cite
|
Sign up to set email alerts
|

Changes in B-Readings Over Time in the United States Navy Asbestos Medical Surveillance Program

Abstract: Changes from previous B-readings are common, and may have clinical and other implications, which are discussed. B-readings should not be used as the sole basis for determining the presence or absence of pneumoconiosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2008
2008
2011
2011

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 10 publications
(14 reference statements)
1
1
0
Order By: Relevance
“…About 15 % of occupationally exposed individuals who demonstrated radiographic abnormalities consistent with asbestosis, showed no visible pleural plaques on radiographs. Autopsy studies have shown that pleural plaques are much more common than asbestosis and are present in most asbestosis cases, but may be too small to be seen on radiographs (6,(12)(13). Our results are in accordance with previous reports.…”
Section: Resultssupporting
confidence: 83%
“…About 15 % of occupationally exposed individuals who demonstrated radiographic abnormalities consistent with asbestosis, showed no visible pleural plaques on radiographs. Autopsy studies have shown that pleural plaques are much more common than asbestosis and are present in most asbestosis cases, but may be too small to be seen on radiographs (6,(12)(13). Our results are in accordance with previous reports.…”
Section: Resultssupporting
confidence: 83%
“…Corporate monitoring, medical surveillance, environmental monitoring, and a number of individual surveys play a significant role in providing useful information for the purposes of prevention and decision-making (3,12,56,87,96,109,138). The National Health and Nutrition Examination Survey has provided nationallevel estimates of the biomarkers of exposure for many chemicals in the U.S. population.…”
Section: Other Important Activitiesmentioning
confidence: 99%